Migrant workers and social security protections in Malaysia - Mohamad Amin, Noor Shuhadawati (IIUM Press, International Islamic University Malaysia, 2017)
Social security is one of the vital human rights enunciated in the Universal Declaration of Human Rights of 1948. Despite having the principle of equality of treatment embodied in the Federal Constitution and become signatories to a few international social security related instruments, Malaysia who relies heavily on the migrant workers in various sectors, has yet to accord them the same level of social security protection enjoyed by the local workers. This can be seen from the fragmentation of employment injury schemes with different benefits under two different laws namely the Employees’ Social Security Act 1969 governing the local workers and the Workmen’s Compensation Act 1952 governing the migrant workers in which the latter is inferior to that of the former. Further, the non-mandatory contribution of the migrant workers for the old-age benefits in the Employees Provident Fund 1991 is exacerbated by the low amount of contribution on the part of the employer